2016
DOI: 10.1177/0748233715569269
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity in male mice after exposure to high molybdenum and low copper concentrations

Abstract: To evaluate the effects of dietary high molybdenum (HMo) and low copper (LCu) concentrations on reproductive toxicity of male mice, 80 mice were divided into 4 groups of 20. These groups were fed with the following: (1) normal control (NC) diet (NC group); (2) NC and HMo diets (HMo group); (3) LCu diet (LCu group); and (4) HMo and LCu diets (HMoLCu group). On the 50th and 100th day, superoxide dismutase (SOD), malondialdehyde (MDA), glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Cu deficiency is rare due to the high availability of this element in food [170]. Cu deficiency may lead to pancytopenia and the occurrence of hypodermic anemia which does not respond to the administration of Fe [171,172], loss of appetite [173], damage to internal organs [174,175], bone deformities [176], reduced reproductive capacity [177], myocardial fibrosis [178,179], and chronic debilitating diarrhea [180]. It may lead to neurological disorders, and hair depigmentation [181,182].…”
Section: Copper (Cu)mentioning
confidence: 99%
“…Cu deficiency is rare due to the high availability of this element in food [170]. Cu deficiency may lead to pancytopenia and the occurrence of hypodermic anemia which does not respond to the administration of Fe [171,172], loss of appetite [173], damage to internal organs [174,175], bone deformities [176], reduced reproductive capacity [177], myocardial fibrosis [178,179], and chronic debilitating diarrhea [180]. It may lead to neurological disorders, and hair depigmentation [181,182].…”
Section: Copper (Cu)mentioning
confidence: 99%
“…Lower concentrations of this mineral in the milk can be considered an advantage of the Alberta milk, since a glass of milk provides less than 20% of its RDI. Due to negative implication of excessive intakes of Mo on reproductive functions of males [36,37], lower amounts of Mo in the Alberta raw milk make it a safe product to consume [38].…”
Section: Discussionmentioning
confidence: 99%
“…Atli et al (2006) demonstrated that Cu accumulation causes an increase in ROS, leading to oxidative stress in fish. ROS are composed of hydroxyl radicals, superoxide anions, and their byproducts, which can cause toxicity, including lipid peroxidation, DNA fragmentation, and protein oxidation (Wang et al 2016). MDA, the stable metabolite of lipid peroxidation, is considered a reliable parameter that reflects the increase in ROS, and an increase in the level of MDA is related to oxidative damage (Zhao et al 2020).…”
Section: Cu-induced Hepatic Histopathology and Liver Impairment In Swamp Eelmentioning
confidence: 99%